The Correlation between Metacognitive Skills and Critical Thinking Skills toward Students’ Process Skills in Biology Learning - Lusia Naimnule; Aloysius Duran Corebima (Journal of Pedagogical Research, 2018)
The purpose of this correlational research was to determine the correlation between metacognitive skills and critical thinking skills toward the process skills of Senior High School students through the implementation of inquiry, REACT, and inquiry integrated with REACT learning models. The population of this research was all students of class X Senior High Schools in Malang in the 2017/2018 academic year. The samples used in this research were the class X students of Science 1 of Senior High School 8 Malang, Science 2 of Senior High School 8 Malang, and science 3 of Senior High School 5 Malang. The research data were analyzed by using multiple regression correlation analysis. The results of this research show that there is a correlation between metacognitive skills and critical thinking skills toward the students’ process skills through the implementation of the Inquiry learning model, REACT and INREACT. The contributions of metacognitive skills and critical thinking skills toward the students’ process skills through the implementation of Inquiry, REACT and INREACT learning models are 64,7%, 81,3% and 72,5% respectively. This indicates that the effective contribution through the REACT learning model is higher than that through the Inquiry and INREACT learning models.